Performance of Acacia Gum as a Novel Additive in Thin Film Composite Polyamide RO Membranes - Yehia Manawi (14152704) (2019)
Novel thin film composite (TFC) polyamide (PA) membranes blended with 0.01–0.2 wt.% of Acacia gum (AG) have been prepared using the interfacial polymerization technique. The properties of the prepared membranes were evaluated using contact angle, zeta potential measurements, Raman spectroscopy, scanning electron microscopy, and surface profilometer. It was found that the use of AG as an additive to TFC PA membranes increased the membrane’s hydrophilicity (by 45%), surface charge (by 16%) as well as water flux (by 1.2-fold) compared with plain PA membrane. In addition, the prepared PA/AG membranes possessed reduced surface roughness (by 63%) and improved antifouling behavior while maintaining NaCl rejection above 96%. The TFC PA/AG membranes were tested with seawater collected from the Arabian Gulf and showed higher salt rejection and lower flux decline during filtration when compared to commercial membranes (GE Osmonics and Dow SW30HR). These findings indicate that AG can be used as an efficient additive to enhance the properties of TFC PA membranes. Other Information Published in: Membranes License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/membranes9020030